Pengembangan metode pembelajaran quantum teaching sistim tandur untuk meningkatkan hasil belajar Pendidikan Agama Islam kelas VII di SMP Negeri Dlanggu Kabupaten Mojokerto - ikmal, happy (Sekolah Tinggi Ilmu Tarbiyah Raden Wijaya Mojokerto, 2017)
There is a paradoxical state between individual achievement and institutional quality. Why when in other countries Indonesian people are able to perform well, while in their own country is not. For that is the time we rise rescue the children of this country with a positive education, applicative and normative. Changes the paradigm that education is with 3D (Sit, Silence, Listen), which is very fooling child. School-based learning tends to be very theoretical and unrelated to the environment in which the child is located, resulting in the child being unable to apply what he or she learns in school in order to solve life problems faced in daily life. From the problems that the purpose of this research development are: 1) To determine the feasibility of RPP / Scenario learning Quantum teaching system tandur subjects Islamic Religious Education class VII SMP Negeri Dlanggu Mojokerto regency according to Expert. 2) To know the feasibility of LKS learning method of learning Quantum teaching system tandur subjects Islamic Religious Education class VII SMP Negeri Dlanggu Mojokerto regency according to colleagues 3) To know the interest of students to RPP learning model Quantum teaching system tandur subjects Islamic Religious Education class VII in SMP Negeri Dlanggu Kabupaten Mojokerto. The selection and use of teaching materials of Islamic Religious Education of learning method of quantum teaching of tanding system can effectively streamline and streamline the implementation of learning. For that purpose the teaching materials of Islamic Religious Education of quantum teaching method of tandur system is absolutely necessary. The teaching material of Islamic Religious Education of teaching method of quantum teaching of this tandur system has been refined based on analysis of trial data. Based on the steps that have been implemented can be concluded as follows. 1). According to the Expert RPP / Scenario learning Quantum teaching system tandur subjects Islamic Religious Education class VII SMP Negeri Dlanggu Mojokerto decent enough to use 2) According to colleagues LKS learning learning method Quantum teaching system tandur subjects Islamic Religious Education class VII SMP Negeri Dlanggu Mojokerto decent Used. 3) RPP learning model Quantum teaching system of subject matter of VII Islamic Religion Education at State Junior High School Dlanggu Mojokerto Regency appeals to students